Cultural Values and Social Capital in Empowering Migrant Fishers: A Case Study of the Butonese in Derawan, Indonesia (Proceeding International Collaborative Conference on Multidisciplinary Science, 2025)
Migrant fishers are among the most vulnerable groups in Indonesia’s coastal economy, facing ecological uncertainty, market volatility, and limited institutional recognition. Yet, their survival and empowerment often depend not only on economic resources but also on cultural values and social capital that regulate cooperation, solidarity, and adaptation. This paper examines how Butonese migrant fishers in Derawan, Berau Regency, East Kalimantan construct empowerment through everyday practices and community-based institutions. The study employs a qualitative case study approach, combining in-depth interviews, focus group discussions, participant observation, and document analysis. Data were analyzed thematically with guidance from Kabeer’s empowerment framework, Putnam’s social capital theory, and Parsons’ AGIL model. Findings reveal four interrelated dynamics. First, cultural values such as mosinte (mutual help) and spiritual practices serve as adaptive mechanisms and informal safety nets. Second, social capital enables collective empowerment through rotating savings groups, cooperative labor arrangements, and trust-based conflict resolution. Third, integration is reinforced by solidarity practices like gotong royong, rituals, and cultural events, which sustain legitimacy and cohesion. Finally, cultural values undergo transformation (latency) as kinship ties and rituals are reinterpreted into collective enterprises and hybrid institutions that secure recognition from external actors. The study concludes that empowerment among migrant fishers is not only economic but also cultural and relational. Strengthening cultural institutions and social capital is essential for building resilience, fostering inclusivity, and ensuring sustainable fisheries governance in Indonesia.